2022
DOI: 10.3390/plants11020210
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exogenously Sprayed Antioxidants on Physio-Biochemical, Agronomic, and Quality Parameters of Potato in Salt-Affected Soil

Abstract: Salinity is one of the harsh environmental stresses that destructively impact potato growth and production, particularly in arid regions. Exogenously applied safe–efficient materials is a vital approach for ameliorating plant growth, productivity, and quality under salinity stress. This study aimed at investigating the impact of foliar spray using folic acid (FA), ascorbic acid (AA), and salicylic acid (SA) at different concentrations (100, 150, or 200 mg/L) on plant growth, physiochemical ingredients, antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…The major vital components of the BHS have previously been used individually as foliar applications with success supporting plant performance and increasing its resistance to stress, e.g., organic acids [ 63 ], soluble sugars [ 64 , 65 ], amino acids [ 66 , 67 , 68 ], proline [ 66 , 69 ], essential nutrients [ 70 , 71 , 72 ], ascorbate [ 73 ], B-group vitamins [ 74 , 75 ], selenium [ 7 ], and iodine [ 76 ]. In this paper, all of these components are combined into a solution (BHS) in organic forms, giving this solution a multi-mechanism for plants to adjust to stress conditions and resist stress via signaling pathways and efficient mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The major vital components of the BHS have previously been used individually as foliar applications with success supporting plant performance and increasing its resistance to stress, e.g., organic acids [ 63 ], soluble sugars [ 64 , 65 ], amino acids [ 66 , 67 , 68 ], proline [ 66 , 69 ], essential nutrients [ 70 , 71 , 72 ], ascorbate [ 73 ], B-group vitamins [ 74 , 75 ], selenium [ 7 ], and iodine [ 76 ]. In this paper, all of these components are combined into a solution (BHS) in organic forms, giving this solution a multi-mechanism for plants to adjust to stress conditions and resist stress via signaling pathways and efficient mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, crops cannot be cultivated if soil salinity is not controlled and rises above specified salinity thresholds ( FAO, 2017 ). Among abiotic stresses, salinity affects plant growth by hampering photosynthesis, CO 2 assimilation and excessive ROS production ( Chaudhary and Choudhary, 2021 ; ElSayed et al, 2021 ; Selem et al, 2022 ). The detrimental effects of salinity begin with osmotic or water stress (a reduction in the root’s ability to absorb water), followed by ionic toxicity (nutritional imbalance, formation of ROS species), hormonal imbalance and susceptibility to infection by the pathogen ( Choudhary et al, 2017 ; Talbi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Abo-Baker and Mostafa [ 96 ] revealed that the application of B. polymyxa and Azospirillum increased anthocyanin, vitamin C, and the total acidity in roselle. In a similar vein, Selem et al [ 97 ] found that spraying potato with ascorbic and salicylic acids significantly increased the plant-soluble sugars and total carbohydrates in the tubers.…”
Section: Discussionmentioning
confidence: 83%